Eu, o professor : um estudo sobre desenvolvimento profissional de professores de educação física em início de carreira - Gomes, Luciane de Almeida (2019)
This work consists in a report of research developed in the range of the Post Graduation Program in Education of the Federal University of Mato Grosso, in a doctorate degree, in the research line of School Cultures and Languages and has as aim to comprehend how the teachers of Physical Education in the beginning of the career transform their formative experiences and become teachers, in a path of professional development. Specifically, it is aimed to comprehend how the teachers of Physical Education in beginning of the career transform their formative experiences and organize their pedagogical composition; to identify how the teachers learn the teaching in a school, and how their path makes them participants of this investigative process, that assume the reflection as mediator of the professional development of these ‘new’ teachers; to analyze how the personal and formative experiences influence the organization of teachers’ pedagogical practice; to comprehend how they occupy their position in school and how the articulation happens with the peers; to identify how the teachers organize and live the continued formation. To fulfill the mentioned aims, we undertook the critical research-action with the collaborative approach as methodological orientation, as well as their emancipation conditions: the collaboration; successive cycles of critical reflection; involvement of the participants in the research activities. The research had as collaborators: four teachers of Physical Education in beginning of career, egress of the Bachelor Course of Physical Education of the Physical Education College of UFMT, that have in common the participation as scholarships’ students in PIBID – Institutional Program of Scholarship of Induction to Teaching and that, in the year of 2017, completed one year of teaching in a city school of Cuiabá, which started in the second semester of 2016. The spaces of negotiation and reflection produced by the methodological path were considered as locus of the research and happened in and outside the school, in different conditions of organization, from the reflections about the meanings that the participants produced about the practice individually and collectively. The project predicted two mediating devices: the Collaborative Observation and the Cycles of Reflexive Studies. The focal group also was used as complementary mediating device, with the aim of evaluating the research’s path. In each month cycles of observation were done, during three weeks, followed by a cycle of reflection, in the forth week, considering that the registers of the observations were object of reflection. The path made us see the complexity and the challenges of the beginning years of the career and to indicate the emergency of programs of professional induction that contemplate the necessity to follow, to support and to promote non technical learning about the profession, enhanced from the interactions that happen inside the school. Mediated by reflective processes we assumed a higher capacity of reflecting about how the practices of Initial and Continued Formation of teachers can be. We can reflect more adequately about what to expect of the University in a program of Initial Formation and what needs to be considered in the Continued Formation of teachers.